IMPACT OF PRINCIPALS’ LEADERSHIP STYLES AND TEACHERS’ WORK MOTIVATION ON TEACHER PERFORMANCE AT STATE VOCATIONAL HIGH SCHOOLS IN TANA TORAJA REGENCY - Darma Pala’langan; Tita Rosita; Kabul Wahyu Utomo (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Improving the quality of public vocational high schools (SMK Negeri) is strongly influenced by teacher performance. Two factors frequently associated with such performance are the principal’s leadership style and teachers’ work motivation. This study examines the effects of principals’ leadership style and teachers’ work motivation on teacher performance in public vocational high schools in Tana Toraja Regency. Employing a quantitative approach, the research used a survey design with 106 respondents drawn from four public vocational high schools in Tana Toraja Regency. The questionnaire instrument used a Likert scale and was subjected to validity and reliability testing. Data were analyzed using multiple linear regression with the model: Y = –2.450 + 0.152X₁ + 0.328X₂ + ϵ.The results indicate that both leadership style and work motivation have a significant effect on teacher performance, with work motivation exerting a stronger influence than leadership style. Partially, leadership style significantly predicts performance (t = 6.665; p < 0.001), and work motivation also significantly predicts performance (t = 12.367; p < 0.001). Correlation analysis shows positive relationships between leadership style and performance (r = 0.652), leadership style and motivation (r = 0.453), and motivation and performance (r = 0.818).These findings underscore the importance of democratic leadership practices and motivation enhancing policies such as recognition, professional development, and a supportive work environment to sustain consistent teaching performance in vocational education.